Frequency domain image analysis for the characterization of porous products. (December 2016) - Grassini, S.; Pisano, R.; Barresi, A.A.; Angelini, E.; Parvis, M.
Highlights: New way of estimating the mass transfer coefficient suitable for industrial plants. Suitable for pharmaceutical drug production monitoring. Provides information at vial level. Based on SEM and a frequency domain imaging process. Overcome the limitation of current batch level solutions. Abstract: Many pharmaceutical products are obtained via freeze-drying of liquid solutions to obtain stable long lasting preparations. The freeze-dry process produces porous cakes whose structure strongly depends on the freezing phase, so that monitoring and optimizing this phase can help both reducing the product cost and insuring its constant quality. Nowadays the optimization is usually performed by determining the cake mass transfer coefficient via a costly process in pilot plants, while the quality is assured only by controlling the process conditions. This paper describes an alternative way of approximately estimating the mass transfer coefficient, which is based on the observation of the product structure by a simple electron microscope followed by a frequency domain imaging process. While the process has been designed and characterized specifically for pharmaceutical products, the proposed approach can be used in several other fields where the characteristics of porous material have to be monitored.